A comparison of the intraspecific variability of Phlebotomus sergenti Parrot, 1917 (Diptera: Psychodidae) - Dvorak, V; Aytekin, A M; Alten, B; Skarupova, S; Votypka, J; Volf, P (Journal of vector ecology, 2006)
Phlebotomus sergenti populations from different areas of the Mediterranean basin are known to exhibit high intraspecific variability. Previous studies of ITS2 revealed the presence of two branches that may represent sibling species. To corroborate this finding by other tools, two colonies of P. sergenti originating from Turkey and Israel, each belonging to a different ITS2 branch, were compared by three different methods: geometric morphometric analysis of wing shape, RAPD (random amplified polymorphic DNA), and cross-mating study. For geometric morphometric analysis, two-dimensional Cartesian coordinates of 16 landmarks from the wings were digitized and analyzed. Significant shape differences were found between colonies but not between sexes within each colony. RAPD results formed two distinctive clades corresponding to the origin of the colony but also showed heterogenity among members of both colonies. In cross-mating studies, viable hybrid F1 and F2 progeny were obtained when both Turkish males/Israeli females and Israeli males/Turkish females were crossed. F1 progeny was included in RAPD analysis and these hybrids formed a distinctive clade with an intermediate position between the two parental clades. No significant differences were found in egg production of crossed sand flies. The cross-mating study showed that there is no reproductive barrier between P. sergenti from different geographical areas. On the other hand, RAPD and geometric morphometric analysis revealed a significant difference between colonies and confirmed the suitability of previous ITS2 analysis for discrimination among sand fly populations. Further development of molecular markers should resolve a possible existence of sibling species within Phlebotomus sergenti.
Keywords: Hybridization, Genetic; Random Amplified Polymorphic DNA Technique; Genetic Speciation; technika náhodné amplifikace polymorfní DNA; druhová specificita; hybridizace genetická; Male; Animals; Genetic Variation; Female; mužské pohlaví; ženské pohlaví; genetická variace; zvířata; vznik druhů (genetika); Species Specificity; Phlebotomus